2014
DOI: 10.1186/1748-717x-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy with simultaneous integrated boost for locoregionally advanced nasopharyngeal carcinoma

Abstract: ObjectiveTo compare the treatment outcomes of intensity-modulated radiotherapy with simultaneous integrated boost (IMRT-SIB) alone to concurrent chemoradiotherapy (CCRT) for locoregionally advanced nasopharyngeal carcinoma (NPC).MethodsFrom November 2001 to December 2009, 333 patients with pathologically diagnosed, locoregionally advanced NPC were treated by IMRT-SIB with or without weekly cisplatin concurrent chemotherapy at our institute. Among them, 62 patients received neo- or adjuvant chemotherapy or mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
1
45
1
Order By: Relevance
“…The acute toxicity with grade 3 or more was low in our patients and no treatment interruption of SIB‐VMAT was observed during CCRT course. Grade 3 mucositis was experienced in 10.7% of our patients, which is lower than the results (16.0%‐34.9%) in NPC patients treated by CCRT with SIB‐IMRT . With a primary focus on sparing the parotids, many clinical studies have proved the significant reduction of xerostomia after IMRT relative to the conventional technique .…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The acute toxicity with grade 3 or more was low in our patients and no treatment interruption of SIB‐VMAT was observed during CCRT course. Grade 3 mucositis was experienced in 10.7% of our patients, which is lower than the results (16.0%‐34.9%) in NPC patients treated by CCRT with SIB‐IMRT . With a primary focus on sparing the parotids, many clinical studies have proved the significant reduction of xerostomia after IMRT relative to the conventional technique .…”
Section: Discussioncontrasting
confidence: 61%
“…IMRT or VMAT may be applied in the conventional fractionation scheme with sequential shrinkage phases, or a newer fractionation scheme, known as simultaneously integrated boost (SIB), which offers the opportunity to treat different targets simultaneously at different dose levels. The application with SIB planning, compared to sequential planning, has the advantages of providing higher dose per fraction to the tumor with shorter overall treatment time and has become a popular fractionation strategy in treating NPC, especially for those with locally advanced tumor . As far as we know, a comprehensive outcome analysis for NPC patients treated by CCRT with the technique of SIB‐VMAT was scarcely reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early results from this trial suggest that ACT may not be beneficial in this group of patients. A recent retrospective study by Yi et al (2014) found the outcomes of advanced NPC treated by cisplatin-based CCRT alone were poorer among patients treated by radical IMRT; the OS, disease-free survival (DFS) and DMFS rates were 71.7, 63.9 and 79.6%, respectively. No significant differences in survival between CCRT and radiotherapy alone in patients with stage III-IVb disease treated by radical IMRT have been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Thirty (73 %) patients After the completion of chemotherapy, patients underwent radiation therapy to the head and neck region performed uniformly with IMRT. Details regarding the radiation techniques have been previously reported [14,15]. Briefly, the total dose to the primary gross tumor (GTVnx), the involved cervical lymph nodes (GTVnd), the subclinical regions at high risk of involvement (PTV1) and the low-risk lymph nodal regions (PTV2) were 70-76, 70, 60 and 50-54 Gy, respectively.…”
Section: Treatmentmentioning
confidence: 99%